2019
DOI: 10.13057/biodiv/d200232
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Phenotypic diversity of male Burgo chicken from Bengkulu, Indonesia

Abstract: Abstract. Setianto J, Sutriyono, Prakoso H, Zain B, Adwiyansyah R, Amrullah AHK. 2019. Short Communication: Phenotypic diversity of male Burgo chicken from Bengkulu, Indonesia. Biodiversitas 20: 532-536. Burgo chicken is the result of a crossbreed of Red Junglefowl (Gallus gallus gallus) with Kampung chicken (Gallus domestica). This study aimed to describe the diversity of colors found in male Burgo chickens. The study was conducted in the city of Bengkulu, Indonesia. The method used in this study was a direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
2
0
2
Order By: Relevance
“…An assessment of the variation in the qualitative phenotypical characteristics found that KT chickens in the regions of the study predominantly had Jak Kod Hna comb, red earlobes, orange around the eyes, brown beak, brownyellow neck and back plumage, red wing plumage, blackgreen long curving and back tails, grey shanks, normal spur type, and Plod scale type. These results were similar to those reported by Dorji et al (2012) and Setianto et al (2019). However, Charoensook et al (2020) showed that Kai Tang's beautiful neck feature was golden or red color and the ear patches on the sides of the head were red or white.…”
Section: Qualitative Phenotypical Characteristicssupporting
confidence: 85%
See 1 more Smart Citation
“…An assessment of the variation in the qualitative phenotypical characteristics found that KT chickens in the regions of the study predominantly had Jak Kod Hna comb, red earlobes, orange around the eyes, brown beak, brownyellow neck and back plumage, red wing plumage, blackgreen long curving and back tails, grey shanks, normal spur type, and Plod scale type. These results were similar to those reported by Dorji et al (2012) and Setianto et al (2019). However, Charoensook et al (2020) showed that Kai Tang's beautiful neck feature was golden or red color and the ear patches on the sides of the head were red or white.…”
Section: Qualitative Phenotypical Characteristicssupporting
confidence: 85%
“…Moreover, the Department of Livestock Development (2021) reported that some breeds of Kai Tang had red earlobes and the same color of beak, eyes and shank. Additionally, Setianto et al (2019) revealed that in the wild, the red color of red junglefowl helped chickens to disguise their body color with dry leaves when threatened with predators. The current genetic purity of red junglefowl ranges from 92% to 93.75% (Brisbin et al 2005).…”
Section: Qualitative Phenotypical Characteristicsmentioning
confidence: 99%
“…Nusantara yang berada di sepanjang garis khatulistiwa menyimpan banyak sekali kekayaaan fauna berupa spesies hewan yang belum banyak digali informasinya oleh para peneliti. Spesies hewan yang berpotensi untuk dikembangkan sebagai ternak unggas lokal di Pulau Sumatera adalah ayam Burgo (Putranto et al, 2018;Setianto et al, 2019). Ayam Burgo yang selanjutnya disebut dengan Burgo atau Berugo merupakan ayam atau unggas eksotik dan endemik di Provinsi Bengkulu (Putranto et al, 2018(Putranto et al, , 2017(Putranto et al, , 2016(Putranto et al, , 2012aPutranto, 2011;Setianto et al, 2019).…”
Section: Pendahuluanunclassified
“…Spesies hewan yang berpotensi untuk dikembangkan sebagai ternak unggas lokal di Pulau Sumatera adalah ayam Burgo (Putranto et al, 2018;Setianto et al, 2019). Ayam Burgo yang selanjutnya disebut dengan Burgo atau Berugo merupakan ayam atau unggas eksotik dan endemik di Provinsi Bengkulu (Putranto et al, 2018(Putranto et al, , 2017(Putranto et al, , 2016(Putranto et al, , 2012aPutranto, 2011;Setianto et al, 2019). Bahkan dalam rangka menyongsong kegiatan Wonderful Bengkulu 2020, Pemerintah Provinsi Bengkulu telah menetapkan ayam Burgo atau Berugo atau Brugo sebagai salah satu ikon kegiatan berdampingan dengan ikon bunga Raflesia (Anonim, 2019).…”
Section: Pendahuluanunclassified
“…Based on the conservation status issued by IUCN (International Union for the Conservation of Nature and Natural Resources) on the IUCN Red List, the status of the red jungle fowl is included in LC (Least Concern) status or low risk [16].The Red jungle fowl is one of the wildlife that live in forests and plantations in Bengkulu, Sumatra, Indonesia and plays an important role in producing new poultry species [6,17,18]. The result of matting between red jungle fowl and local chicken has produced offspring called burgo chicken which is a Bengkulu's local chicken [9,12,19]. The red jungle fowls and their offspring are exploited by humans as pets with the aim of being a genetic source, food source, ornamental animals, and hunting animals.…”
Section: Introductionmentioning
confidence: 99%